Multi-locus sequence analysis reveals profound genetic diversity among isolates of the human pathogen Bartonella bacilliformis. - Gemma L Chaloner; Palmira Ventosilla; Richard J Birtles (Public Library of Science (PLoS), 2011)
Bartonella bacilliformis is the aetiological agent of human bartonellosis, a potentially life threatening infection of significant public health concern in the Andean region of South America. Human bartonellosis has long been recognised in the region but a recent upsurge in the number of cases of the disease and an apparent expansion of its geographical distribution have re-emphasized its contemporary medical importance. Here, we describe the development of a multi-locus sequence typing (MLST) scheme for B. bacilliformis and its application to an archive of 43 isolates collected from patients across Peru. MLST identified eight sequence types among these isolates and the delineation of these was generally congruent with those of the previously described typing scheme. Phylogenetic analysis based on concatenated sequence data derived from MLST loci revealed that seven of the eight sequence types were closely related to one another; however, one sequence type, ST8, exhibited profound evolutionary divergence from the others. The extent of this divergence was akin to that observed between other members of the Bartonella genus, suggesting that ST8 strains may be better considered as members of a novel Bartonella genospecies.